Uptake and utilization of deoxynucleoside 5'-monophosphates by Mycoplasma mycoides subsp. mycoides. - Neale, G A (1984)
Mycoplasma mycoides subsp. mycoides has been shown to possess an unusual capacity for the uptake and utilization of exogenous deoxyribonucleoside 5'-monophosphates intact without prior dephosphorylation. In this study, it was found that once inside the cell, deoxyribonucleoside 5'-monophosphates were rapidly phosphorylated to the triphosphate level and incorporated into DNA. Catabolism of deoxyribonucleoside 5'-monophosphates was also observed. Competition studies indicated that a single uptake system with a higher affinity for deoxyribonucleotides mediates the uptake of nucleoside 5'-monophosphates.